2018
DOI: 10.1161/jaha.118.008997
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating Adipokines With Echocardiographic Measures of Cardiac Structure and Function in a Community‐Based Cohort

Abstract: BackgroundAdipokines mediate cardiometabolic risk associated with obesity but their role in the pathogenesis of obesity‐associated heart failure remains uncertain. We investigated the associations between circulating adipokine concentrations and echocardiographic measures in a community‐based sample.Methods and ResultsWe evaluated 3514 Framingham Heart Study participants (mean age 40 years, 53.8% women) who underwent routine echocardiography and had select circulating adipokines measured, ie, leptin, soluble l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 59 publications
3
23
1
Order By: Relevance
“…38,39 Likewise, the Framingham Heart study found no relationship between FS and leptin levels. 18 Nonetheless, our study showed a significant relationship between leptin levels and GLS in healthy obese participants. The mechanism whereby high leptin levels alter cardiac function remains unclear, but it is hypothesized that leptin may be involved in cardiac myocyte hypertrophy, sympathoactivation, increased total peripheral resistance, oxidative stress, and/or alterations in fatty acid metabolism.…”
Section: Leptin and Cardiac Functioncontrasting
confidence: 50%
See 2 more Smart Citations
“…38,39 Likewise, the Framingham Heart study found no relationship between FS and leptin levels. 18 Nonetheless, our study showed a significant relationship between leptin levels and GLS in healthy obese participants. The mechanism whereby high leptin levels alter cardiac function remains unclear, but it is hypothesized that leptin may be involved in cardiac myocyte hypertrophy, sympathoactivation, increased total peripheral resistance, oxidative stress, and/or alterations in fatty acid metabolism.…”
Section: Leptin and Cardiac Functioncontrasting
confidence: 50%
“…Our results supported the findings of a communitybased study, which found the inverse relationship between leptin and LVMI and LA diameter as well as the MESA study. 18,33 In contrast, some evidence shows that leptin levels are positively associated with ventricular mass in hypertensive patients and in morbid obesity. 34,35 The dissimilar results in these clinical studies are probably due to the differences in comorbidity, duration of being obese, and/or serum leptin levels of the participants.…”
Section: Leptin and Cardiac Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…These last observations may be explained by the above-mentioned data concerning the effect of adiposity (FM, VAT and EAT) on heart remodelling [7,25]. The influence is related to a direct paracrine effect of EAT, the thickness of which correlates with visceral adiposity, as well as the endocrine and proinflammatory activity of VAT [10][11][12]26]. The results of this study have some limitations.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the associations between heart dimensions and nutritional status are complicated by the distribution of adiposity, which an example is the relationship between epicardial adipose tissue (EAT) and left atrial size that was found to be positive for patients with paroxysmal AF and negative for patients with permanent AF [10]. Such effect of fat tissue on heart remodelling and risk of arrhythmia is explained by its paracrine, endocrine and proinflammatory properties [10][11][12]. These data suggest that the association between heart morphology and function and patient nutritional status may be more complicated than simply a relationship with body size or body surface area (BSA).…”
Section: Introductionmentioning
confidence: 99%